Contact angle of NіTі alloy surfaces after face milling - N.O. Balytska (Технічна інженерія, 2025)
Wettability is an important functional property of a surface that is of fundamental importance in many fields of science and technology, from mining to biomedicine. NiTi alloys are becoming increasingly used in various industries, which requires the investigation of their wetting properties after various technological processing methods. Different machining methods create a specific microrelief on the surface, which is one of the key factors affecting the wetting properties of the surface. This work is devoted to the experimental investigation of the dependence of the contact angle of NiTi alloy surfaces after face milling on the parameters of roughness and waviness measured in different directions relative to the feed direction. The test specimens were machined under conditions of dry symmetrical face milling with variable cutting conditions. The contact angle of the surface was determined by the sessile drop method. The water droplet was in the Wenzel state on all milled surfaces under study. The influence of surface topology on the drop shape is considered. A sample with a polished surface (Ra 0.07 μm) is used as a reference for comparison. The correlations between the roughness and waviness of milled surfaces measured in different directions and the contact angle are discussed. The results can be useful for understanding the wetting behavior of milled surfaces made of NiTi alloys.